The Influence of Employee Work Professionalism on the Quality of Public Services at the Tuwung Village Office, Barru District, Barru Regency. - Az, Wahyul; Hj.Aidah (P3M Stia Al Gazali Barru and Meraja media, 2024)
[Full Paper] to pdf Copyright (c) 2024 Meraja journal